Factors Influencing Health Insurance Participation Among Bentor Drivers in Gorontalo Regency - Yusuf, Barmin Rahmat; Yakup, Anggita Permata; Novriansyah, Moh Arif; Ibrahim, Ismail A. (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study examines the factors influencing the participation of Bentor drivers in the National Health Insurance (JKN) program in Gorontalo Regency. Using a logistic regression model, the findings indicate that age and mobile phone ownership significantly impact JKN enrollment, whereas education, income, and distance to healthcare facilities do not show a meaningful effect. These results suggest that awareness and accessibility play a more crucial role in shaping participation decisions than traditional socioeconomic factors. The increasing use of mobile technology highlights its potential in expanding JKN coverage. Individuals with mobile phones have better access to information and a more convenient registration process, which increases their likelihood of joining the program. Meanwhile, the non-significant effect of education and income implies that knowledge about JKN is not solely dependent on formal education or financial capacity. Policy implications from this study emphasize the need for digital-based outreach programs to enhance awareness of JKN benefits. Social media, mobile applications, and online registration systems can improve access and facilitate a more efficient enrollment process. Furthermore, targeted policies for informal workers, including incentives or simplified administrative procedures, may encourage broader participation. In conclusion, JKN participation is driven more by access to information and ease of registration than by socioeconomic status. Strengthening digital initiatives and designing inclusive policies can significantly improve JKN coverage, ensuring better healthcare protection for all segments of society. This study provides valuable insights for policymakers in developing more effective strategies to enhance healthcare accessibility in Indonesia.